Recovery of Polysaccharides from Red Grape Marc and White Grape Pomace by Degradation of Cell Walls by Enzymes with Different Activities - Ekhiñe Garaigordobil; Leticia Martínez-Lapuente; Zenaida Guadalupe; Silvia Pérez-Magariño; Belén Ayestarán (Molecules)
The recovery of polysaccharides (PS) from red grape marc and white grape pomace by enzymatic degradation of their cell walls is an interesting green extraction technique that preserves the structure and bioactivity of PS. The type and dose of enzyme, and the liquid/solid (L/S) ratio in PS extraction were studied using four commercial enzymes. Four different doses per enzyme were used, with tartaric acid as solvent and L/S ratios of 1.3/1 and 4/1 for 24 h at 20 °C, compared with a control. The highest dose of enzyme E1, polygalacturonase + pectin lyase + pectin-methyl-esterase (with the highest activity) was the most effective in the degradation of high and medium molecular weight PS. At the lower L/S ratio, the fact that the highest dose of E1 degraded a higher percentage of high and medium molecular weight PS in the marc was explained by the difference in cell wall deconstruction between pomace and marc. The highest total PS purity was achieved in pomace with E1 at the maximum dose in both ratios, and in marc at the 1.3/1 ratio. The extraction efficiency of total PS was low for all enzymes. In the future, extraction with E1 combined with other green extraction techniques will be studied.